The impact of EMA recommendations on the real-life use of Janus kinases inhibitors for rheumatoid arthritis: the Expanded Risk Score in RA as a tool to quantify the risk of cardiovascular events - Favalli, Ennio Giulio; Cincinelli, Gilberto; Germinario, Sabino; Di Taranto, Raffaele; Orsini, Francesco; Maioli, Gabriella; Biggioggero, Martina; Ferrito, Matteo; Caporali, Roberto (Frontiers in Immunology, 2023)
Objective: To evaluate in patients with rheumatoid arthritis (RA) the impact of EMA recommendations on the real-life prescription of JAK inhibitors (JAKis) and the use of the Expanded Risk Score in RA (ERS-RA) to quantify the risk of major adverse cardiac events (MACE).We conducted a retrospective analysis of real-life RA patients treated with JAKis.Patients were classified as ineligible for JAKis if they fulfilled EMA criteria (>65 years-old, history of malignancy, or increased risk of venous thromboembolic events [VTE] or MACE including smoking). Risk of MACE was defined according to ORAL Surveillance trial inclusion criteria (ORALSURV) or by using the ERS-RA.Results: Of 194 patients enrolled, 57.9% were classified as ineligible according to EMA definition (ORALSURV criteria). The most frequent reason for ineligibility was increased MACE risk (70.2%), followed by age>65 (34.2%), smoking (30.7%), and increased risk of VTE (20.2%) or malignancy (7%). The use of the ERS-RA reduced the rate of patients carrying an increased CV risk to 18.6% (p<0.001 versus ORALSURV), leading to 46.4% overall ineligible patients. Over a drug-exposure of 337 patient/years, we observed 2 VTE, one MACE (non-fatal stroke), and one solid malignancy (all in the group of patients classified as ineligible according to both the definitions).Conclusions: Rigorous application of EMA indications in clinical practice could result in the exclusion of a large proportion of RA patients from treatment with JAKis. A proper quantification of the risk for MACE by dedicated tools as ERS-RA is advocated to better tailor the management of RA.